Enantioselective Functionalization of Prochiral Cyclobutanones and Cyclobutenones - Wang, Meng; Zhong, Changxu; Lu, Ping (Synlett, 2021)
Enantioselective synthesis of cyclobutane derivatives is still a challenging topic in asymmetric synthesis. [2+2] Cycloaddition and skeleton rearrangement are two primary strategies to this end. Recently, functionalization of cyclobutanones and cyclobutenones, which are readily available via [2+2] cycloadditions as prochiral substrates, has emerged as a powerful tool to access versatile four-membered ring compounds. Herein, we summarize some recent advances in these areas from our and other groups.1 Introduction2 Enantioselective Functionalization of Cyclobutanones2.1 Chiral Lithium Amide Approach2.2 Enamine Approach3 Enantioselective Functionalization of Cyclobutenones4 Conclusion
Keywords: cyclobutanone; cyclobutenone; desymmetrization; conjugate addition; chiral lithium amide; enantioselective reduction